A Study of Linguistics Landscape Towards Tourism Enterpreneur Language Ability at Simanindo District, Samosir Regency, North Sumatera Province - Rahmat Darmawan (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2017)
This research is aim for finding and describing the language skill of tourism actor in Simanindo sub-district which reflected on the results of using language in public by using linguistic landscape approach or known as LL. The research method which used in this research is descriptive and qualitative method. Basically, qualitative method observe the use of language on LL, review the form and meaning of language morphology and multilingual morphological situation as an international tourist area. In this research we observed that the use of language in all public spaces included street names, welcome greetings, directions, tourism business signs and so on and provided questionnaires for tourism actors regarding language skills. By using qualitative method, Data obtained will be fuller, deeper, trustworthy and meaningful so that the research objectives can be achieved. The findings of the research: language morphology dominated by the form of words and phrases. In the linguistic situation  the most dominant form of bilingual are mixing between the use of Indonesian and English. The meaning of the language contained in LL in Simanindo District is oriented to denotative and connotative meaning. Somewhat rare idiomatic meaning for dominant use of language in the LL is informative. The language skills of tour operators are generally still lacking. This is evident from the morphology of words, phrases, clauses and sentences in Indonesian and English by not applying the rules of writing and good translation. There is a difference between the use of LL made by the government and private institutions. LL by the government has uniformity at the linguistic and non-linguistic level while the independent tourism actors tend to produce the original language according to the wishes of each local community. This becomes significant with the language as the first component encountered by tourists in the tourist area. Language will determine whether the tourists will linger or leave the area immediately. Recommendation: (1) It should be a good linguistic planning of the use of language in the LL in Simanindo. (2) The need to reduce the language awareness of tourism. (3) It should be cooperation between the relevant institutions to provide training and counseling language in favor of language skills (language competence) tourism actors.